The Chemo-physical properties of camel (camelus bactrianus) urine in the Gobi Desert (Mongolian Journal of Agricultural Sciences, 2022)
Camels with two humps /Camelus bactrenus/ are distributed in small numbers across Central Asia, and can  particularly be found in the Mongol mountains of the Gobi and in the provinces of southern China. We carried out research to study the physical and chemical properties of urine of two-humped camels /Camelus bactrenus/ adapted to the Gobi Desert region of Mongolia. In our research, copper in the urine of Umnugovi province camels was not detected, but the copper content detected in the urine of 10 camels from Dornogovi province was similar to that of one-humped Arabian camels. The concentration of zinc in the urine of some camels was 7 to 8 times greater than that of Arabic camels.Mонгол тэмээний шээсний физик, хими шинж чанарыг судалсан дүнХоёр бөхт тэмээ нь төв Ази, тэр дундаа Монголын говь, Хятад улсын өмнөд муж нутгаар цөөн тоогоор тархсан байдаг. Бид Монголын говь цөлийн бүсэд дасан зохицсон хоёр бөхт тэмээний шээсний физик, хими  шинж чанарыг судлах зорилгоор судалгааны ажлыг гүйцэтгэв. Бидний судалгаагаар Өмнөговь аймгийн тэмээний шээсэн дэх зэсийн агууламж илэрсэнгүй, харин Дорноговь аймгийн 10 тэмээний шээсэн дэх зэсийн агууламж Арабын нэг бөхт тэмээтэй ойролцоо байсан. Зарим тэмээний шээсэн дэх цайрын агууламж Арабын нэг бөхт тэмээнээс 7-8 дахин өндөр байлаа. Түлхүүр үг: Тэмээ, шээс, өнгө, өтгөн, нягт